Gauging the Nexus of Policy and Regulatory Framework on Environmental Sustainability and Renewable Energy in Nigeria - Hussaini Bala; Aliyu Abdullahi; Hassan Bala; Noor Afza Amran; Arma Ya’u Alhaji Sani; Raziqa Muhammad Shafiu; Hasnah Shaari; Fatima Alti Idris (Yustisia, 2025)
Nigeria has a renewable energy strategy and regulatory framework for optimal usage that ensures environmental sustainability and economic progress. This study analyses Nigeria's renewable energy regulatory framework and environmental sustainability. The article used doctrinal and empirical research. The Nigerian renewable energy regulatory system was qualitatively analysed using the doctrinal method. World Bank 2002–2021 data was used for the empirical technique.Renewable Energy Consumption significantly impacts environmental sustainability. As GDP is high, renewable energy usage and environmental sustainability are more linked. Introducing a new renewable energy strategy and regulatory framework improved renewable energy use. This study will assist Nigerian and international authorities like the World Bank modify and adopt regulations to promote renewable energy usage and environmental quality.